Molecular characterization of GDP mannose pyrophosphorylase, GDP-mannose-3',5'-epimerase and galactose-1phosphate uridylyltransferase recombinant proteins from Gracilaria changii I. abbott - Siow, Rouh San (2012)
Gracilaria changii is a red seaweed which grows in the muddy and silted mangroves fringing the west coast of Peninsular Malaysia such as Morib, Selangor.Gracilaria plays an important role in the phycocolloid industry for agar production. GDP-mannose pyrophosphorylase (GMP), GDP-mannose-3’, 5’-epimerase (GME) and galactose-1-phosphate uridylyltransferase (GALT) are the enzymes involved in the biosynthesis of D- and L-galactose (basic unit of agar). Although the complete biosynthetic pathway of agar and agarose biosynthesis is not known, the regulating steps of agar and agarose biosynthesis is believed to lie in the intermediate pathways involving the biosynthesis of UDP-D and GDP-L-galactose. The objectives of this study were to express the cDNAs encoding GcGALT, GcGME and GcGMP as recombinant protein in Escherichia coli for biochemical assays and to isolate the 5’flanking regions of these three enzymes from G. changii. The recombinant proteins of GcGALT and GcGME were successfully expressed as soluble proteins in E. coli strain BL21 (DE3) pLysS. The enzyme activity of recombinant GcGALT was determined in a coupled assay by monitoring the reduction of NAD and NADP. For the forward reaction, the Km (UDP-glucose) and Km(galactose-1-phosphate) were 0.134 mM and 0.116 mM, respectively. For the reverse reaction, Km(glucose-1-phosphate) and Km(UDP-galactose) were 0.092 mM and 0.051 mM, respectively. The analysis of high performance liquid chromatography (HPLC) showed that the purified recombinant GcGME formed two products, most probably GDP-Lgalactose and GDP-L-gulose. The recombinant protein of GcGMP was expressed as inclusion bodies in E. coli strain Origami (DE3) pLysS. The inclusion bodies were solubilized and refolded for enzyme assay using HPLC. However, the refolded recombinant GcGMP did not show any activity. The structural gene sequences of GcGALT, GcGME and GcGMP isolated from the genomic DNA of G. changii were devoid of introns. Cis-acting regulatory element related to light, methyl jasmonate responses and meristem specific activation/expression were found at the 5’ flanking regions of GcGALT, GcGME and GcGMP. The cis-acting regulatory element involved in light response showed the highest frequency in the 5’ flanking regions of GcGALT, GcGME and GcGMP. The molecular and biochemical haracterization of recombinant GcGALT, GcGME and GcGMP may facilitate the understanding of agar production in G. changii.